IMPROVING COMMUNICATION SKILLS WITH E-MODULE ASSISTED SIMULATION FOR OFFICE MANAGEMENT STUDENTS OF SMK TEUKU UMAR SEMARANG - Kusumaningrum, Selvy; Oktarina, Nina; Kuswantoro, Agung (Universitas Negeri Semarang, 2025)
This study aims to develop an e-module–assisted simulation learning model to enhance the communication skills of Office Management students at SMK Teuku Umar Semarang, where existing learning practices do not employ simulation-based approaches and the learning resources used are not yet aligned with students’ needs. Using a Research and Development (R&D) design, the study adopts the 4D development model—Define, Design, Develop, and Disseminate—to produce and validate the proposed learning innovation. The subjects of this research were Grade XI students in the Office Management expertise competency. Product feasibility was assessed by two material experts and one media expert, followed by limited and extended trials to evaluate the e-module’s effectiveness. The results show that current Communication in the Workplace learning does not provide sufficient opportunities for students to practice workplace communication and lacks integration with interactive digital resources. The developed e-module received a validation score of 96% from material experts and 100% from media experts, indicating strong feasibility for instructional use. Trial findings further demonstrated substantial improvements in student learning outcomes, with average N-Gain scores of 0.751 in the limited trial and 0.791 in the extended trial. In conclusion, the e-module is effective and suitable as a digital learning medium to support simulation-based instruction and strengthen students’ communication skills. These results highlight the potential of technology-supported simulation models to enhance vocational education quality and better prepare students for workplace communication demands